Functional Dyspesia: Functional Dyspepsia and serology - Crafa, Pellegrino; Franceschi, Marilisa; Rodriguez Castro, Kryssia Isabel; Barchi, Alberto; Russo, Michele; Franzoni, Lorella; Antico, Antonio; Baldassarre, Gianluca; Panozzo, Maria Piera; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2020)
Dyspepsia is a functional GI disorder consisting in a wide range of symptoms. The main diagnostic challenge has been whether to perform an EGD or an abdominal US in order not to miss organic lesions, but to avoid unnecessary and sometimes invasive tests. Pepsinogen serology has been proposed as an useful non-invasive test to explore the status of the gastric mucosa, suggesting this strategy as an adequate approach in management of dyspepsia. In a primary care setting, 266 dyspeptic patients were investigated to establish the proper diagnosis. The workup included upper GI endoscopy with biopsies, a structured questionnaire including type and severity of symptoms, serological determination of serum pepsinogens, gastrin 17 and IgG against Hp. Inclusion criteria were dyspeptic symptoms (epigastric pain, nausea and/or vomiting, post prandial fullness, early satiation) lasting more than 1 year and the association between symptoms and food ingestion.. Helicobacter pylori infection was present in 114 subjects, characterized by high levels of pepsinogen II and IgG against Hp. Twenty subjects were classified according with the diagnosis of chronic body atrophic gastritis. Nausea and post prandial fullness were the most frequent symptoms (48% and 41%, respectively) in the studied population, followed by epigastric pain and early satiation (37% and 26% respectively). A diagnosis of normality by serological diagnosis was found in half of patients experiencing epigastric pain and in about 60% of subjects with the three other symptoms (nausea, post prandial fullness, and early satiation). In conclusion, this experience confirms the clinical usefulness of serology in dyspepsia, contributing to correctly diagnosing CAG and H.p. infection in such patients and providing a good correlation with the clinical picture.